Clinical and therapeutic features of myasthenia gravis in adults based on age at onset. (17th March 2020) - Cortés-Vicente, Elena; Álvarez-Velasco, Rodrigo; Segovia, Sonia; Paradas, Carmen; Casasnovas, Carlos; Guerrero-Sola, Antonio; Pardo, Julio; Ramos-Fransi, Alba; Sevilla, Teresa; López de Munain, Adolfo; Gómez, Maria Teresa; Jericó, Ivonne; et al.
Abstract : Objective: To describe the characteristics of patients with very-late-onset myasthenia gravis (MG). Methods: This observational cross-sectional multicenter study was based on information in the neurologist-driven Spanish Registry of Neuromuscular Diseases (NMD-ES). All patients were >18 years of age at onset of MG and onset occurred between 2000 and 2016 in all cases. Patients were classified into 3 age subgroups: early-onset MG (age at onset <50 years), late-onset MG (onset ≥50 and <65 years), and very-late-onset MG (onset ≥65 years). Demographic, immunologic, clinical, and therapeutic data were reviewed. Results: A total of 939 patients from 15 hospitals were included: 288 (30.7%) had early-onset MG, 227 (24.2%) late-onset MG, and 424 (45.2%) very-late-onset MG. The mean follow-up was 9.1 years (SD 4.3). Patients with late onset and very late onset were more frequently men ( p < 0.0001). Compared to the early-onset and late-onset groups, in the very-late-onset group, the presence of anti–acetylcholine receptor (anti-AChR) antibodies ( p < 0.0001) was higher and fewer patients had thymoma ( p < 0.0001). Late-onset MG and very-late-onset MG groups more frequently had ocular MG, both at onset (<0.0001) and at maximal worsening ( p = 0.001). Although the very-late-onset group presented more life-threatening events (Myasthenia Gravis Foundation of America IVB and V) at onset ( p = 0.002), they required fewer drugs ( p < 0.0001) and were less frequently drug-refractory ( p < 0.0001). Conclusions: Patients with MG are primarily ≥65 years of age with anti-AChR antibodies and no thymoma. Although patients with very-late-onset MG may present life-threatening events at onset, they achieve a good outcome with fewer immunosuppressants when diagnosed and treated properly.